2019
DOI: 10.1097/md.0000000000014391
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation with simultaneous use of red and infrared light emitting diodes in the treatment of temporomandibular disorder: study protocol for a randomized, controlled and double-blind clinical trial

Abstract: Introduction: Temporomandibular disorder (TMD) is considered the main cause of orofacial pain of non-dental origin, and a public health problem. The symptomatology is muscular and/or articular pain, restriction of the mandibular range of motion, and changes in the mandibular movement pattern. Due to its complexity there are already treatments using various forms of therapy. Photobiomodulation using light sources, such as low-level laser or light emitting diodes (LED), with different wavelengths, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
1
10
0
3
Order By: Relevance
“…Thus, 51 articles were assessed based on eligibility criteria. Seven studies were excluded due to the following reasons: two studies presented with a study protocol only [50,51], and one study each was excluded for the following reasons: subjects with mean age below 18 year old [52]; laser acupuncture [53]; TMJ magnetic resonance imaging (MRI) for diagnosis of TMD [54]; TMJ osteoarthritis with fossa ad condyle changes [55]; and utilisation of combined physiotherapeutic, pharmacotherapy and homeopathic measures [56] (inter-reviewer agreement, κ = 1). Consequently, 44 out of 51 full text articles were included and analysed in the present systematic review .…”
Section: Study Selectionmentioning
confidence: 99%
“…Thus, 51 articles were assessed based on eligibility criteria. Seven studies were excluded due to the following reasons: two studies presented with a study protocol only [50,51], and one study each was excluded for the following reasons: subjects with mean age below 18 year old [52]; laser acupuncture [53]; TMJ magnetic resonance imaging (MRI) for diagnosis of TMD [54]; TMJ osteoarthritis with fossa ad condyle changes [55]; and utilisation of combined physiotherapeutic, pharmacotherapy and homeopathic measures [56] (inter-reviewer agreement, κ = 1). Consequently, 44 out of 51 full text articles were included and analysed in the present systematic review .…”
Section: Study Selectionmentioning
confidence: 99%
“…Despite these differences, both types of lasers have a photodynamic effect (e.g., photons activate mitochondria) (16,17), which has been thought to be the basis of the therapeutic effect of laser irradiation. LLLT has been applied to treat temporomandibular disorder (18) and endodontic and periodontal diseases (17) in dentistry, and an analgesic effect of LLLT on orthodontic force-induced pain has been reported, although not consistently (11,12,19,20). To evaluate the analgesic effect quantitatively and to elucidate the appropriate CO 2 or diode laser irradiation strategy for orthodontic force-induced pain, the changes in jaw-opening reflex excitability caused by laser irradiation were measured in the experimental tooth movement (ETM) animal model.…”
Section: Introductionmentioning
confidence: 99%
“…The main signs and symptoms are muscle and joint pain, noises in the joints (cracking and/or clicking), restriction of jaw range of motion, and changes in jaw movement pattern. It can present with tinnitus, vertigo, lack of muscular coordination and biomechanical imbalance of the cervical region (2). In addition, a variety of other symptoms can occur, such as abnormal swallowing and tenderness of the hyoid bone; these symptoms can compromise quality of life and even sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of LLLT that have been highlighted are analgesics and anti-inflammatories (11). According to various studies, LLLT has shown beneficial results with respect to pain derived from DTM (2)(3)(4)(11)(12)(13)(14)(15)(16); it resulted in the immediate reduction of painful symptoms and a greater range of movements mandibular in the treated group (12). However, for others the LLLT has not shown be more effective than other therapies to simultaneously resolve both pain and impairment of orofacial functions in DTM (13).…”
Section: Introductionmentioning
confidence: 99%